Personality and gender of people training in Kyokushin karate and kickboxing - Piepiora, P.; Komarnicka, N.; Gumienna, R.; Maslinski, J. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2022)
Background and aim. Kickboxing is a full-contact combat sport that has evolved from the knockdown formula characteristics of Kyokushin karate. The aim of the article was to attempt to determine the personality of people training in Kyokushin karate and kickboxing. Material and method. The study involved people practicing Kyokushin karate (n1 = 30) and kickboxing (n2 = 30) aged 18 to 29. There were 15 women and 15 men in each sample. The NEO-FFI Personality Questionnaire [Costa Jr., McCrae 2007] was the method used. Results. The personalities of the karate Kyokushin and kickboxing athletes were at a similar level in all personality dimensions: low neuroticism, high extraversion and conscientiousness, average openness to experience and agreeableness. But women (in general) were more neurotic, extroverted, and conscientious and less open to experiences in relation to men; agreeableness was at a similar level. Women training in Kyokushin karate were more neurotic and conscientious, and less open to experience than men from the same combat sports. Women training in kickboxing were more extroverted and conciliatory to men in the same combat sports. Conclusions. People competing in the knockdown formula are no different from those competing in the full contact formula and from athletes from other disciplines in all personality traits. Gender is an important personality determinant among combat sports practitioners.